The Influence of Implementation of Risk Management and Corporate Governance with Bank Size as an Intervening Variable on Banking Financial Performance (Analytical Study on Sharia Banking Listed on the Indonesian Stock Exchange) - Khalisah Visiana; Ni Made Yulia Permatasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine whether Risk Management and Corporate Governance with Bank Size as an intervening variable on the financial performance of banking companies listed on the IDX, to determine whether Risk Management and Corporate Governance affect the financial performance of banking companies listed on the IDX through Bank Size as an intervening variable to find out whether Risk Management and Corporate Governance affect Bank Size in banking companies listed on the IDX and to determine whether Bank Size affects financial performance in banking companies listed on the IDX. The population used in this study is four banking companies listed on the Indonesia Stock Exchange. Using the purposive sampling method according to the criteria, there are four selected banking companies. Using the 2016 to 2020 observation year (5 years) to measure discretionary accrual plus the 2015 observation year, it will get 30 data observations as sampling in this study. Hypothesis testing is done by linear regression analysis. From the results of hypothesis testing, it is known that the application of risk management has a significant effect on financial performance and corporate governance has a significant effect on financial performance. Moreover, the application of risk management using Bank Size as an intervening variable can mediate financial performance, and the implementation of corporate governance using Bank Size as an intervening variable can mediate company performance, meaning that Bank Size is not a good variable in mediating the relationship between risk management and corporate governance. Financial Performance (KK) and Risk Management affect earnings management, while Corporate Governance affects Bank Size, and Bank Size affects financial performance.